COVID-19 Rapid Antigen Test as Screening Strategy at Points of Entry: Experience in Lazio Region, Central Italy, August–October 2020 - Francesca Colavita; Francesco Vairo; Silvia Meschi; Maria Beatrice Valli; Eleonora Lalle; Concetta Castilletti; Danilo Fusco; Giuseppe Spiga; Pierluigi Bartoletti; Simona Ursino; Maurizio Sanguinetti; Antonino Di Caro; et al. (Biomolecules, 2021)
COVID-19 pandemic is a dramatic health, social and economic global challenge. There is urgent need to maximize testing capacity. Rapid Antigen Tests (RAT) represent good candidates for point-of-care and mass surveillance testing to rapidly identify SARS-CoV-2-infected people, counterbalancing lower sensitivity vs. gold standard molecular tests with fast results and possible recurrent testing. We describe the results obtained with the testing algorithm implemented at points of entry (airports and ports) in the Lazio Region (Italy), using the STANDARD F COVID-19 Antigen Fluorescence ImmunoAssay (FIA), followed by molecular confirmation of FIA-positive samples. From mid-August to mid-October 2020, 73,643 RAT were reported to the Regional Surveillance Information System for travelers at points of entry in Lazio Region. Of these, 1176 (1.6%) were FIA-positive, and the proportion of RT-PCR-confirmed samples was 40.5%. Our data show that the probability of confirmation was directly dependent from the semi-quantitative FIA results. In addition, the molecularly confirmed samples were those with high levels of virus and that were actually harboring infectious virus. These results support public health strategies based on early mass screening campaigns by RAT in settings where molecular testing is not feasible or easily accessible, such as points of entry. This approach would contribute to promptly controlling viral spread through travel, which is now of particular concern due to the spread of SARS-CoV-2 variants.